Phytochemical Screening, Antioxidant, Antibacterial, and α-Amylase Inhibitory Activity of Moringa oleifera Lam. Leaves - Kalauni, Surya Kant; Khanal, Lekh Nath; Thapa, Prakash; Kunwor, Keshari (Journal of Nepal Chemical Society, 2023)
Moringa oleifera is a perennial deciduous plant abundant in tropical countries that contains many important bioactive compounds. This study aimed to evaluate phytochemical analysis, antioxidant, antibacterial, and α-amylase inhibitory activities of the methanol and hexane leaf extracts of the plant collected from Nepal. Phytochemical screening of the extracts revealed the presence of a wide spectrum of secondary metabolites such as alkaloids, flavonoids, phenolics, saponins, tannins, terpenoids, etc. Methanol and hexane extracts showed the presence of significant quantities of total phenolics (207.75± 2.75 mg GAE/g, and 137.09 ± 1.1 mg GAE/g) and total flavonoids (94.56 ± 1.88 mg QE/g, and 82.71 ± 1.47 mg QE/g) respectively. The methanol extract exhibited higher 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity. The half-maximal concentration causing 50% inhibition of the radical (IC50) of methanol and hexane extracts was 39.19 ± 0.33 and 61.07 ± 1.46 μg/mL respectively which are comparable to that of standard ascorbic acid (28.90 ± 0.24 μg/mL. Methanol extract of M. oleifera leaves showed moderate antibacterial activity against Staphylococcus aureus (ATCC25923), Bacillus cereus, and Klebsiella pneumonia (ATCC700603). In-vitro antidiabetic activity was performed by a starch-iodine method using α-amylase enzyme and methanol extract showed significant antidiabetic activity (IC50 value 31.78 ± 0.52 μg/mL). The results of this study corroborate the potential application of the plant in traditional medicine and the drug discovery process.